Anand's human anatomy for dental students - Anand, Mahindra Kumar (Jaypee Brothers Medical Publishers, 2012)
The third edition of Anand's Human Anatomy for Dental Students is a comprehensive guide to every part of the human anatomy. Beginning with a section on general and systemic anatomy, the book goes on to discuss the head and neck, histology, genetics, embryology and radiological anatomy. Over 1000 illustrations enhance learning and the section on histology includes photographs of slides featuring every tissue and organ, along with a corresponding illustrated diagram. Each section includes review questions to assist revision.